2019
DOI: 10.1038/s41385-019-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

A pro-inflammatory CD8+ T-cell subset patrols the cervicovaginal tract

Abstract: The immune system of the cervicovaginal tract (CVT) must balance immunosurveillance and active immunity against pathogens with maintenance of tolerance to resident microbiota and to fetal and partner antigens for reproductive purposes. Thus, we predicted that CVT immunity is characterized by distinctive features compared to blood and other tissue compartments. Indeed, we found that CVT CD8+ T-cells had unique transcriptional profiles, particularly in their cytokine signature, compared to that reported for CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 55 publications
9
24
0
Order By: Relevance
“…We recently reported that memory CD8 T cells in the human CVT displayed unique phenotypical and functional features including the presence of a subset of CD69 − CD103 − inflammatory CD8 T cells (1). Importantly, the majority of memory CD8 T cells in the CVT of healthy women typically expressed CD103 and CD69, which are biomarkers associated with tissue-residence (24), suggesting that most memory CD8 T cells in the human CVT stably reside there.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that memory CD8 T cells in the human CVT displayed unique phenotypical and functional features including the presence of a subset of CD69 − CD103 − inflammatory CD8 T cells (1). Importantly, the majority of memory CD8 T cells in the CVT of healthy women typically expressed CD103 and CD69, which are biomarkers associated with tissue-residence (24), suggesting that most memory CD8 T cells in the human CVT stably reside there.…”
Section: Introductionmentioning
confidence: 99%
“…Within the T cell compartment, a near 1:1 CD4/CD8 T cell ratio was observed in healthy endometrial biopsies at the secretory phase of the menstrual cycle [54][55][56]. This distribution substantially differs from that of blood (in which CD4 T cells are more frequent) and mirrors that of other barrier tissues that are largely populated by Trm cells, including the endocervix, ectocervix, and vagina [45,57,58]. Indeed, endometrial memory T cells (defined by CD45RO positivity) expressed CD69 (and to a lesser extent, CD8 T cells coexpressed CD103) [54] suggesting that Trm cells are present at the window of implantation.…”
Section: Tissue Residency: Preimplantationmentioning
confidence: 93%
“…While most Trm cells have a Tem-like phenotype, those with Temra phenotypes can also contribute to tissue residence [ 58 ], yet do not express CD45RO, potentially explaining the reported CD69 expression in CD45RO − endometrial T cells [ 54 ]. In line with bona fide tissue residence, CD69 + memory T cells isolated from the endometrium express the proteins PD-1 [ 54 ] or CCR5 [ 55 ] and transcripts for CD49a [ 59 ], mirroring phenotypic and transcriptional signatures broadly shared by human Trm cells across mucosal and lymphoid tissues [ 45 , 49 , 57 ]. While CCR5 expression has long been associated with a Th1 phenotype [ 60 ], a recent study demonstrated that CCR5 + CD4 T cells in healthy and inflamed human barrier tissue are actually potent IL-17 producers [ 45 ].…”
Section: The Memory T Cell Compartment Changes During the Course Omentioning
confidence: 99%
See 1 more Smart Citation
“…CD69 + CD103 − CD8 + Trm cells are also present in the stroma of various tissues, such as the skin, gut, FRT, salivary gland, and brain (Wakim et al 2010;Bergsbaken and Bevan 2015;Smith et al 2015;Thom et al 2015;Watanabe et al 2015;Pattacini et al 2019). A CD103 − CD8 + Trm cell population has also been described in the brain (Wakim et al 2010).…”
Section: Stromal Cd8 + Trm Cell Subpopulationsmentioning
confidence: 99%